Contestation Between Buzzer Accounts In The Arena Of The 2024 Presidential Election On Instagram Social Media - Fakihani, Mukhamad; Falaakh, Mohammad Fajrul; Imawan, Khaerudin; Lestari, Aghnia Dian (ann4publisher@gmail.com, 2024)
Social media, especially Instagram, is a contest for buzzers in the 2024 presidential and vice presidential elections. In debates on social media, they are free to express their support in any way. Likewise content, but not necessarily hoax content, is sent to attract sympathizers due to the existence of an ITE law that prevents the spread of hoaxes, especially since this is an official buzzer account, likewise, in this election, which was attended by 3 pairs of candidates and vice presidents where there must be contestation from the three candidates who need an increase in electability to win this presidential election. This research method uses qualitative techniques, such as observation techniques, for data collection. Aim to see if the public is affected in the content created by the buzzer account. With this, the results of the study show that positive content is given from the 3 official buzzers, which apply the concepts of habitus, field, and capital, which cause the impact of buzzer dominance on Instagram social media does not have a strong influence on the results of the 2024 election, and it is the public's view of which leader will be chosen that is higher.